Post-Pandemic Internet Addiction (ProblemAnalysisandAlleviation Strategy Through Guidance and CounselingServices) - Yulitri, Rina; Nisa, Fadillatul (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
The number of internet users continues to experience a significant increase fromyear to year. This is clear evidence that the existence of the internet is at the top of the hierarchy of human needs today. Students' status as digital natives with high internet access intensity raises concerns about the continuity of their education. This is because there is high interaction with the internet which can make students experience internet addiction. This research aims to analyze internet addiction problems experienced by students and what strategies are used by guidance andcounseling teachers at schools. This research was conducted at MTsN 2 Pesisir Selatan. The researchmethod used is a qualitative method with a case study approach. From the results of the researchconducted, it is known that there are 6 problems experienced by students due to internet addiction, namely: 1) decreased learning achievement; 2) undisciplined behavior; 3) online game addiction; 4) misuse of social media; 5) cyberbullying; and 6) pornography addiction. The strategies used by guidance and counseling teachers to help students overcome their internet addiction include: 1) Classical guidance; 2) Cross-class guidance; 3) Group guidance; 4) Development of comic media; 5) Individual counseling; 6) Group counseling; 7) Home visits; and 8) Google form based problembox.